(untitled) (Indian Journal of Public Health Research & Development, 2020)
To investigate the awareness and improvement requirements of this study was conducted on college students who were the beginnings of adulthood and who were subject to scaling health insurance. Subjects were divided into health and non-health college students to investigate the perception of whether or not to apply scaling health insurance, payroll costs, and the number of benefits. In addition, this study was conducted to provide basic data for the long-term scaling health insurance business to become a social system for improving the quality of life of the people The subjects of this study were to have health and non-health college students respond to the questionnaire from October 10th to October 23rd, 2019 by using the self-assessment writing method and the total of 341 questionnaire was analyzed as the final subject. Cross-analysis was used to verify the difference in perception of the presence or absence of scaling to the general characteristics of the study subjects, and t-test was used to verify the difference in the recognition score for the detailed criteria of scaling insurance. The significance level of the collected data was verified at p<0.05. Recognition of scaling benefits was high in 32.5% of health and 25.7% of non-health college students and the awareness of detail was low in all items. In the improvement requirements, the highest response from both health and non-health sectors were that to increase the number of scaling which is covered in dental insurance in south Korea more than once per year. Looking at the needs of health-related and non-health related college students for the scaling health insurance benefit project, 16.2% of respondents wished to increase the number of times applied per year, 11.7% needed business promotion, 11.2% answered it should included the stain removal (colorants), 9.2% wished age-reduced relief for the business, 6.6% for the cost adjustment in the health-related college student. To raise awareness about scaling salary among college students, it is necessary to recognize the importance of oral health through education and promotion on scaling. In order to raise awareness about scaling insurance among college students, it is necessary to recognize the importance of oral health through education and promotion of scaling. Through this study, it is thought that the scaling health insurance reimbursement project will contribute to the improvement of oral health of the people and furthermore to a healthy life. In the future, the government should continue to develop policies to promote oral health by collecting thoughts and opinions of college students and others as well.